Erich Kistler et al. (eds). Sanctuaries and the power of consumption. Networking and the formation of elites in the Archaic western Mediterranean world / Gocha R. Tsetskhladze et al. (eds). The Danubian lands between the Black, Aegean, and Adriatic Seas (7th centuries BC–10th century AD). - Donnellan , Lieve (Journal of Greek Archaeology, 2016)
Last year saw the appearance of the eagerly-expected acts of two conferences on the archaeology of seas, or connected seascapes: physical spaces joined together by interaction and exchange over sea, rather than over land. The first volume’s aim is more narrow, with a focus on sanctuaries as a stage and instrument of elite interaction and the maintenance of power in the Archaic western Mediterranean, whereas the second book’s much broader theme is the Danube region and its wider geographical context, of the Black Sea between the 7th centuries BC–10th century AD.